(:unas) unassigned - Georgiadou, Olga (My University, 2018)
Research on the possibilities offered by Moodle platform in terms of online learning, interaction, evaluation, task delivery by creating a French as a Foreign Language course on Moodle and by integrating it on a FFL 1st and 2nd level course.